Comparison study of fault location on distribution network using PSCAD and DIgSILENT power factory by using matching approaches - Lilik J. Awalin; Tasnim Tasnim; Tay Lea Tien; Hadi Suyono (Institute of Advanced Engineering and Science, 2020)
This paper presents the comparative study between PSCAD and DIgSILENT in order to detect fault location on underground distribution network. If a fault occurs in the distribution network, it will generate the voltage dips and over current. It is possible to record the signal output in the primary substation. However, for the research purpose, some of the researcher may use different simulation program. The simulation program may have different performance to generate voltage and current signal when fault simulated. So, it is important to observe the performance of each simulation software. Due to every simulation software may have different advantages, this paper will observe the accuracy of fault distance calculation based on simulation data on the distribution model and when all types of fault are applied to the different simulation program, namely PSCAD and DIgSilent. The matching approach was adopted to calculate the fault distance. To observe the performance of the simulation program, the distance error calculation for every type of fault are compared. By using a matching approach, the PSCAD simulation program produces more accurate fault distance compare with DIgSILENT. However, it may contribute different result if different method and tested network applied.